Factores socio-culturales y violencia contra la mujer en la comuna San José del cantón Santa Rosa, año 2020 - Guerrero Zapata, Nadey Jahayra; Nole Aponte, Ana Graciela (Machala: Universidad Técnica de Machala, 2021)
Violence against women refers to any act that can result in harmful damage to the health of the victims, causing internal or external injuries, affecting their integral development, a phenomenon that has received great attention from the State, academia or society. Within this framework, the theme Socio-cultural factors and violence against women in the San José commune of the Santa Rosa canton, year 2020 has been proposed. In the field of study, a great social problem was detected since there is gender inequality and violence exerted against the female sex, evidenced through various types such as: psychological shouting and insults, physical blows and shoves, sexual and symbolic showing itself in a naturalized and hidden way within homes. These acts of abuse are generated due to the fact that in the locality a macho and patriarchal thinking is maintained, which in turn causes depression, low self-esteem, isolation, anxiety in women, damaging their personal development and intra-family relationship, affecting children in their academic performance. Considering the seriousness of the problem, the necessary measures have not been taken by the pertinent authorities to combat this social phenomenon despite the existence of legal regulations such as, the Constitution of the Republic of Ecuador 2008 or the Comprehensive Organic Law for Prevention and Eradication of Gender Violence against women, which protect and support the rights of victims. In seeking to analyze the phenomenon in question, the objective has been to determine the social dimension acquired by the problem of violence against women generated by the existence of degrading sociocultural practices, taking as a basis the approaches of feminist theory which raises a critical analysis of the gender visions that cause this problem and the struggle to achieve equality between both sexes. The research work carried out has a rational-deductive epistemological approach under whose direction it is sought to analyze the reality of the San José commune, in addition, the qualitative methodological approach was used that allows to describe the phenomenon in depth. For this purpose, techniques and instruments such as in-depth interviews and bibliographic or documentary review were applied through which information was obtained from experiences, opinions and various data. The results obtained showed that there is no empowerment on the part of the female gender characterized by a low perception of their capacities and worth as women, their exclusive dedication to household activities, and economic dependence on men. All this in the context of violence that violates their rights, affects their personal and professional development, preventing them from entering the labor, political and economic field. The intervention proposal has been proposed to develop a community plan for the reduction of violence against women in the San José commune, the same one that is aimed at women, families and the population in general. The proposal includes the development of sensitization and awareness activities with the help of the pro-improvement committee and the Municipal GAD of the Santa Rosa canton to promote a life free of violence and gender equality, achieving a more harmonious and equitable society, aimed at that both men and women have the same life chances.
La violencia contra la mujer se refiere a todo acto que puede tener como resultados daños perjudiciales en la salud de las víctimas ocasionando lesiones internas o externas afectando su desarrollo integral, fenómeno que ha recibido gran atención desde el Estado, la academia o la sociedad. En ese marco se ha planteado como temática Factores socio-culturales y violencia contra la mujer en la comuna San José del cantón Santa Rosa, año 2020. En el campo de estudio se detectó una gran problemática social ya que existe desigualdad de género y violencia ejercida contra el sexo femenino, evidenciada a través de diversas tipologías como, psicológicas gritos e insultos, físicas golpes y empujones, sexuales y simbólicas mostrándose de forma naturalizada y oculta dentro de los hogares. Estos actos de maltrato se generan debido a que en la localidad se mantiene un pensamiento machista y patriarcal, lo que ocasiona a su vez depresión, baja autoestima, aislamiento, ansiedad en las mujeres perjudicando su desarrollo personal y la relación intra-familiar, afectando a los hijos en su desempeño académico. Considerando la gravedad del problema, no se han tomado las medidas necesarias por parte de las autoridades pertinentes para combatir este fenómeno social a pesar de existir normativas legales como, la Constitución de la República del Ecuador 2008 o la Ley Orgánica Integral para la Prevención y Erradicación de la Violencia de Género contra las mujeres, que protegen y respaldan los derechos de las víctimas. Buscando analizar el fenómeno en mención se ha planteado como objetivo determinar la dimensión social que adquiere el problema de la violencia contra la mujer generada por la existencia de prácticas socioculturales degradantes, tomando como base los planteamientos de la teoría feminista la cual plantea un análisis crítico sobre las visiones de género que ocasionan esa problemática y la lucha por conseguir la igualdad entre ambos sexos. El trabajo de investigación realizado tiene un enfoque epistemológico racional-deductivo bajo cuya dirección se busca para analizar la realidad de la comuna San José, además se utilizó el enfoque metodológico cualitativo que permite describir el fenómeno a profundidad. Para el efecto se aplicaron técnicas e instrumentos como entrevistas a profundidad y revisión bibliográfica o documental a través de las cuales se obtuvo información de experiencias, opiniones y datos varios. Los resultados obtenidos demostraron que no existe empoderamiento por parte del género femenino caracterizado por una baja percepción de sus capacidades y valía como mujeres, su dedicación exclusiva a las actividades del hogar, dependencia económica del hombre. Todo ello en el marco de la violencia que vulnera sus derechos, afecta su desarrollo personal y profesional impidiéndole insertarse en el campo laboral, político y económico. Se ha planteado como propuesta de intervención la elaboración de un plan comunitario para la disminución de la violencia contra la mujer en la comuna San José, la misma que este dirigida a mujeres, familias y población en general. La propuesta incluye el desarrollo de actividades de sensibilización y concientización con la ayuda del comité pro-mejoras y el GAD Municipal del cantón Santa Rosa para impulsar una vida libre de violencia y la igualdad de género, logrando una sociedad más armónica y equitativa, tendiente a que tanto hombres como mujeres tengan las mismas oportunidades de vida.
Keywords: VIOLENCIA; MUJER; DESIGUALDAD; GENERO